Luteolin Inhibits Ischemia/Reperfusion-Induced Myocardial Injury in Rats via Downregulation of microRNA-208b-3p. - Chen Bian; Tongda Xu; Hong Zhu; Defeng Pan; Yang Liu; Yuanyuan Luo; Pei Wu; Dongye Li (PLoS ONE)
Background Luteolin (LUT), a kind of flavonoid which is extracted from a variety of diets, has been reported to convey protective effects of various diseases. Recent researches have suggested that LUT can carry out cardioprotective effects during ischemia/reperfusion (I/R). However, there have no reports on whether LUT can exert protective effects against myocardial I/R injury through the actions of specific microRNAs (miRs). The purpose of this study was to determine which miRs and target genes LUT exerted such function through. Methods Expression of various miRs in perfused rat hearts was detected using a gene chip. Target genes were predicted with TargetScan, MiRDB and MiRanda. Anoxia/reoxygenation was used to simulate I/R. Cells were transfected by miR-208b-3p mimic, inhibitor and small interfering RNA of Ets1 (avian erythroblastosis virus E26 (v ets) oncogene homolog 1). MiR-208b-3p and Ets1 mRNA were quantified by real-time quantitative polymerase chain reaction. The percentage of apoptotic cells was detected by annexin V-fluorescein isothiocyanate/propidium iodide dyeing and flow cytometry. The protein expression levels of cleaved caspase-3, Bcl-2, Bax, and Ets1 were examined by western blot analysis. A luciferase reporter assay was used to verify the combination between miR-208b-3p and the 3'-untranslated region of Ets1. Results LUT pretreatment reduced miR-208b-3p expression in myocardial tissue, as compared to the I/R group. And LUT decreased miR-208b-3p expression and apoptosis caused by I/R. However, overexpression of miR-208b-3p further aggravated the changes caused by I/R and blocked all the effects of LUT. Knockdown of miR-208b-3p expression also attenuated apoptosis, while knockdown of Ets1 promoted apoptosis. Further, the luciferase reporter assay showed that miR-208b-3p could inhibit Ets1 expression. Conclusion LUT pretreatment conveys anti-apoptotic effects after myocardial I/R injury by decreasing miR-208b-3p and increasing Ets1 expression levels.